Um modelo baseado em ontologias para representação da memória organizacional - Mauricio Barcellos Almeida (2006)
Nowadays, organizations find themselves in an environment of turbulences, featuring high levels of competitiveness, market integration and a reduction in product life cycles. In such an environment, information and knowledge have become essential for the companies performance. Therefore, discussions have begun on how companies may preserve, for future utilization, the knowledge they hold by adopting knowledge retention structures that try to reproduce human memory characteristics. Inserted in this context, this works main subject is the studying of projects evolving from the practice of retaining knowledge in a corporate environment and of handling mechanisms that are subjacent to the memory of organizations. The notion of memory has been utilized by several authors, who mention the term organizational memory and use it as metaphor to explain certain phenomena perceived within the life cycles of organizations. This research seeks to enrich the discussion onthe memory of organizations. To this end, a model based on human processes and on technological processes has been developed. It is intended to represent organizational memory and, following that, perform an on-site verification as to whether such a model is valid or not. From the point of view of human processes, the model considers the necessity of a uniform organizational language, through which individual knowledge becomes organizational knowledge which may be preserved within the organizational environment. From the point of view of technological processes, the model considers the conception of the knowledge representation component of an architecture calledOMS Organizational Memory System. This component corresponds to an ontology, a structure that is likely to represent the history of an organization and also allows for the creation and maintenance of a uniform organizational language. A representative ontology of the organizational memory, nurtured by the working environment of a realorganization (CEMIG) in which the learned knowledge is formalized and stored, has been conceived. Besides that, an application prototype that enables the displaying of the knowledge preserved in the organizational memory has been developed. The validation of this model is made based on the ontology, as a function of the prototype.